HYDROISOMERIZATION OF CYCLOHEXANE AND N-HEPTANE USING Ni-Mo AND Ni-W CATALYSTS SUPORTED ON SILICA-ALUMINA - A.S. Nasution (Scientific Contributions Oil and Gas, 1987)
An experiment has been carried out to study the influence of hydrogenating site of bi-functional and of butylamine on the hydroisomerization cyclohexane and n-heptane. The observed data show that a high activity of hydrogenating ste of bi-functional catalyst, tends to increase the cataly tic activity of hydroisomeri- zation reaction and n-butylamine acts as catalyst poison, which reduces the isomer products.Â